Overview of Logistics Management Implementation Medical Devices at Mitra Sejati Hospital Medan in 2024 - Putri Mendriani; Mewani Sinaga; Mutiara Salsabila; Fika Ayu Cahaya Hasibuan (Sean Institute, 2025)
This study aims to evaluate the implementation of medical equipment logistics management at Mitra Sejati Hospital Medan in 2024. Using qualitative methods with in-depth interviews of logistics officers, department heads, and related personnel, the research found that the logistics management covered all key stages including selection, planning, procurement, reception, storage, distribution, disposal, control, and administration, all in accordance with the Ministry of Health regulations. Medical equipment selection was based on hospital classification, actual service needs, and official regulatory guidelines, ensuring efficient and effective procurement. Stock management was systematically coordinated quarterly between relevant units and the Health Office to maintain adequate equipment availability. Maintenance and care followed clear Standard Operating Procedures (SOP) with dedicated staff conducting regular calibration and functionality tests. Equipment eligibility certificates were issued in cooperation with the Health Office and technical institutions to guarantee safety and service quality. Equipment damage handling was prompt and coordinated, either through internal repair or collaboration with suppliers, depending on the severity and warranty status. Logistics management evaluation was conducted at least twice a year, with quarterly meetings to address issues and plan continuous improvements. The hospital ensured only certified medical devices with official distribution licenses were used. Operator training and functional testing minimized operational errors. Recommendations include continuous staff capacity building through ongoing training and digitizing logistics management to enhance efficiency and data accuracy. Overall, Mitra Sejati Hospital’s medical equipment logistics management is effective, efficient, and compliant with applicable standards, supporting optimal healthcare service quality.